Sacramental confession and psychotherapy Teleoanalytical-transactional approach to the Christian faith, sin, secret and reconciliation - Maurial Chávez, Iván (2017)
This paper was a reflection on the confession as it is carried out in the Christian-catholic community. The phenomenon was described in an objective way, regardless of any explicit beliefs on the subject. At certain moments, a kind or critical stance was interpreted and, therefore, adopted towards the way the sacrament is carried out. Moreover, some observations were made from the psychology and psychotherapy view about faith, God, demons, guilt, sin, remorse, conversion and forgiveness. The use of training teachers of the Catholic Church was essentially for documentary purposes and does not respond to apologetic interests. The use of biblical quotes aimed at getting a better approach to the Christian message, being aware of the risks involved in such endeavor since manuscripts were transcribed in a different time and with the diverse literary style of each Old testament and Judeo-Christian author. The transactional analysis and the Teleoanalytical psychology are forms of psychology in Adlerian code, which enables to understand the religious phenomenon, recognizing the attitudes and the meaning of conducts both in the priest confessor and in the penitent. In the end, there was some arguing in favor of including therapeutic tools with ludic background, which may facilitate significantly the process of change and personal growth of believers, considering the meaning of their own symbols of reconciliation with the whole or the idea of truth, in such case, God.